2005
DOI: 10.1682/jrrd.2005.01.0023
|View full text |Cite
|
Sign up to set email alerts
|

Video-capture virtual reality system for patients with paraplegic spinal cord injury

Abstract: Abstract-This article presents results from a feasibility study of a video-capture virtual reality (VR) system used with patients who have paraplegic spinal cord injury (SCI) and who need balance training. The advantages of the VR system include providing the user with natural control of movements, the ability to use as many parts of the body as are deemed suitable within the context of therapeutic goals, and flexibility in the way the system can be adapted to suit specific therapeutic objectives. Thirteen par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
98
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(107 citation statements)
references
References 41 publications
(63 reference statements)
2
98
0
7
Order By: Relevance
“…1 Other mechanisms, like normal postural synergies and sensory-motor integration of the lower limbs and trunk, are also impaired. However, it has been proposed that following an SCI, a gradual development of specific motor synergies for balance control in sitting involving even non-postural muscles [2][3][4][5] would lead to reorganisation of the individual's balance control system. 1,6 These strategies are essential, as sitting is one of the most fundamental activities of daily living for persons with SCI 7,8 and this ability determines their level of independence for many activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…1 Other mechanisms, like normal postural synergies and sensory-motor integration of the lower limbs and trunk, are also impaired. However, it has been proposed that following an SCI, a gradual development of specific motor synergies for balance control in sitting involving even non-postural muscles [2][3][4][5] would lead to reorganisation of the individual's balance control system. 1,6 These strategies are essential, as sitting is one of the most fundamental activities of daily living for persons with SCI 7,8 and this ability determines their level of independence for many activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Recovery of balance ability during standing is, therefore, one of the primary and essential aims of rehabilitative programs in individuals with incomplete SCI. These patients are obliged to develop and re-establish compensatory strategies to maintain balance, including activation of appropriate trunk, neck, and upper limbs muscles in response to internal and external postural disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although further studies are needed to investigate a potential association between positive results obtained from laboratory force plate measures and clinical and functional outcomes, 6,9 it has been shown that the main positive effect of such training on postural control can be attributed to sensorimotor integration 5,[10][11][12][13] as well as the coordination improvement because of the task specificity of training. 14,15 In the SCI population, benefits of game-based exercises 16 and virtual reality 3 have been suggested for dynamic sitting balance. These studies have shown their potential for substantial improvements in sitting balance through the inclusion of functional approaches in the training.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,14,15 Single and multiple sessions of VF for balance may improve task performance, [16][17][18][19] static and dynamic sitting balance [16][17][18][19] and may increase practice volume and attention span. 16 Single and multiple sessions of VF for leg muscle functions may increase muscle strength, endurance and ankle joint range of motion, 21 as well as improve gait patterns, gait speed, muscle strength, balance, ankle dorsiflexion (reducing foot drag) and mobility up to 12-16 weeks after training.…”
Section: Outcome Parameters and Resultsmentioning
confidence: 99%